Selecting the best option proposed to construct water reservoir structures using ANP and AHP methods (Case study: Torghabeh and Shandiz) - Afsane Farpoor; abbas khashei siuki (محیط زیست و مهندسی آب, 2017)
Due to the lack of drinking water resources and their importance in the economy of any region, it is vital to locate most suitable place for water storage and water harvesting. Hence, this study was conducted to determine the appropriate places of conservation dams through applying heuristic methods of optimum like AHP and ANP methods in Torghabe and Shandiz located in Khorasan Razavi Province. Selection criteria in this research were five parameters including reservoir volume, reservoir damage, runoff, location, and geology. The research found that eight points in Torghabe and four points in Shandiz have good potential for constructing water reservoir structures. Thus, in Torghabe, a point having higher runoff and reservoir volume compared with the other points was considered as the best place for dam construction. In Shandiz, a point having the highest rating location and geology was proposed as appropriate location for construction. The results showed although ANP method is more advanced than AHP method, both methods have equal value in selecting the best option for constructing the water reservoir.